Seasonal patterns and space‐time clustering of porcine reproductive and respiratory syndrome (PRRS) cases from 2008 to 2016 in Vietnam. Issue 2 (30th January 2019) - Lee, Hu Suk; Pham, Thanh Long; Nguyen, Tien Ngoc; Lee, Mihye; Wieland, Barbara
Summary: Porcine reproductive and respiratory syndrome (PRRS) is an important disease in pig production and is endemic in Vietnam. No nationwide studies have been carried out to understand the spread of PRRS in Vietnam. The main objective of this study was to identify the seasonal patterns and space‐time clusters of PRRS from 2008 to 2016 using national surveillance data in Vietnam. A total of 614, 219 cases were reported during the period. There was a seasonal pattern with single peak by region (except North Central Coast, showing double peaks in March and June). The seasonal plots from the Northern regions showed a higher peak between March and April, whereas the four regions from Southern part displayed a higher peak between June and August. Overall, outbreaks from the northern part of Vietnam tended to occur 3–4 months earlier than the southern part. When the spatial window was set at 50%, space‐time cluster analysis found that the first cluster occurred in the Red River Delta (RRD) (radius: 82.17 km; ratios: 5.5; period: Mar–May/2010) and the second (radius: 50.8 km; ratios: 10.61; period: Aug–Oct/2011) in the Mekong River Delta (MRD) region. Four other clusters were observed in the central and Southern parts. Our findings might provide better insight into the distribution of clusters and temporal patterns of PRRS in Vietnam. This study may provide policy makers with valuable information on the hotspot areas and timing of outbreaks. Also, it identifies when and where national control program could be implemented more efficiently by targeting resources for the prevention and control of PRRS.